Implementing Analytical Hierarcy Process (AHP) Method for Higher Education Competitiveness Development through RAISE++ - Yulmaini -; Siti Kholijah; Anuar Sanusi; M. Ariza Eka Yusendra (Prosiding International conference on Information Technology and Business (ICITB), 2020)
Higher education must have a strategy to be able to compete with other universities. The good method had to be needed to find out the alternative strategies used to improve the competitiveness among higher education. Analytical Hierarchy Process (AHP) method was the decision-making method to obtain alternative strategies that were suitable to the needs of the higher education according to the new paradigm of higher education management. The criteria used in this study were based on RAISE++. There were relevance, academic atmosphere, internal management, sustainability, efficiency and productivity, leadership, access and equity. The relevance had five sub-criteria; the academic atmosphere had four sub-criteria; the internal management had five sub-criteria; the sustainability had four sub criteria; the efficiency and productivity had six sub-criteria; the leadership had five sub-criteria; and, the access and equity had five sub-criteria. The alternative strategy for developing the competitiveness of higher education was through the questionnaires and contained 18 strategies alternative. These alternatives were classified through AHP method. The result of this study was that there were certain alternatives that must be considered for the higher education competitiveness e.g., the management quality, leadership, human resource quality, quality control and evaluation, and good Human Resources investment. These alternatives were regarded as a recommendation for higher education to determine strategies in developing higher education competitiveness.Keywords: Analytic Hierarchy Process, Higher Education Competitiveness, RAISE++